2014
DOI: 10.4304/tpls.4.6.1296-1302
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Language Learning Strategies and Reading Comprehension of Iranian EFL Students Taking Web-based and Face-to-face Instruction

Abstract: Abstract-This study investigated language learning strategies used by EFL web-based learners and face-toface learners. It also examined the difference between pre-test and post-test reading comprehension scores of EFL students who were exposed to web-based and face-to-face instruction. The participants of the study were 200 Iranian EFL university students. They were randomly assigned into two groups, 100 students in one group taking web-based instruction and 100 students in the other group taking face-to-face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, the authors did find average scores for learning anxiety were significantly lower in the F2F instruction group. Ghonsooly and Seyyedrezaie (2014) found that there were no significant differences between the two groups of learners regarding preferences for language learning strategies and reading comprehension. The study measured the outcome of 200 language students with a 50-item translated version of the Strategy Inventory for Language Learning and a test of reading comprehension.…”
Section: No Differencementioning
confidence: 74%
See 2 more Smart Citations
“…However, the authors did find average scores for learning anxiety were significantly lower in the F2F instruction group. Ghonsooly and Seyyedrezaie (2014) found that there were no significant differences between the two groups of learners regarding preferences for language learning strategies and reading comprehension. The study measured the outcome of 200 language students with a 50-item translated version of the Strategy Inventory for Language Learning and a test of reading comprehension.…”
Section: No Differencementioning
confidence: 74%
“…In total, 11 studies, which used standard student performance metrics(e.g. test mark, final grade) found that there were no significant differences between F2F and OL modes (Cavanaugh and Jacquemin, 2015;Driscoll et al, 2012;Ghonsooly and Seyyedrezaie, 2014;Herman and Banister, 2007;Horspool and Yang, 2010;Johnson et al,2000;Pilbeam and Barrus, 2010;Rosell-Aguilar, 2006;Sussman and Dutter, 2010;Woolsey, 2013;Yen et al, 2018). Cavanaugh and Jacquemin (2015) examined a teaching database with information from 140,444 students enrolled across 6,012 university courses and taught by over 100 faculty members between 2010 and 2013. Notable findings were that students with higher GPAs perform even better in online courses or alternatively, struggling students perform worse when taking courses in an online format compared to a F2F format.…”
Section: No Differencementioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have also concluded that there is no significant difference between online and face-to-face instruction for learning languages (Ghonsooly & Seyyedrezaie, 2014 ), evidence-based medicine (Davis et al, 2008 ) fall prevention practices (Maloney et al, 2012 ), and evaluation methodologies (Francescato et al, 2006 ).…”
Section: Online and Face-to-face Learningmentioning
confidence: 99%